Detection of SARS-CoV-2 Genome in Stool and Plasma Samples of Laboratory Confirmed Iranian COVID-19 Patients - Makhmalbaf, Mobin; Hosseini, Seyed Masoud; Aghdaei, Hamid Asadzadeh; Niasar, Mahsa Saeedi; Shoraka, Shahrzad; Yadegar, Abbas; Baradaran Ghavami, Shaghayegh; Shahrokh, Shabnam; Moshari, Mohammadreza; Malekpour, Habib; Zali, Mohammad Reza; Mohebbi, Seyed Reza (Frontiers in Molecular Biosciences, 2022)
Coronavirus disease 2019 (COVID19), caused by the severe acute respiratory syndrome coronavirus 2 (SARSCoV2), was first discovered in China in late 2019 and quickly spread worldwide. Although nasopharyngeal swab sampling is still the most popular approach identify SARS-CoV-2 carriers, other body samples may reveal the virus genome, indicating the potential for virus transmission via non-respiratory samples. In this study, researchers looked at the presence and degree of SARS-CoV-2 genome in stool and plasma samples from 191 Iranian COVID-19 patients, and looked for a link between these results and the severity of their disease. SARS-CoV-2 RNA shedding in feces and plasma of COVID-19 patients was assessed by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Medical data were collected and evaluated, including Clinical features, demographics, radiological, and laboratory findings of the patients. Plasma samples from 117 confirmed laboratory patients were evaluated and 24 out of 117 patients (20.51%) tested positive for SARS-COV-2 RNA. Besides, 20 out of 74 patients (27.03%) tested positive for SARS-COV-2 RNA in stool samples. There seems to be no relationship between the presence of SARS-CoV-2 genome in fecal and plasma samples of Covid-19 patients and the severity of illness. We provide evidence of the SARS-CoV-2 genome presence in stool and plasma samples of Iranian COVID-19 patients.